Nationwide Subjective and Objective Assessments of Potential Talent Predictors in Elite Youth Soccer: An Investigation of Prognostic Validity in a Prospective Study - Höner, Oliver; Murr, Dennis; Larkin, Paul; Schreiner, Robert; Leyhr, Daniel (Frontiers in Sports and Active Living, 2021)
Recent studies have provided empirical evidence on the prognostic relevance of objective performance diagnostics in the soccer talent identification and development process. However, little is known about the prognostic validity of coaches' subjective evaluations of performance. This study evaluated objective and subjective assessments within a nationwide talent development program and addressed motor, perceptual skill, and personality-related performance factors. Male players (N = 13,869; Mage = 12.59 ± 1.07 years) from the age groups U12 to U15 of the German soccer talent development program participated in this study. Participants completed an objective motor diagnostic (sprint, agility, dribbling, ball control, juggling) and were subjectively rated by their coaches (kicking skills, endurance, individual tactical skills, psychosocial skills). All nine predictors were assessed with sufficient psychometric properties (α ≥ 0.72; except dribbling and ball control: α ≥ 0.53). Players' success three seasons later was operationalized by achieving professional youth academy level or not (success rate, 9%). Independent-samples t-tests analyzed univariate mean group comparisons between future selected and non-selected players. Logistic regression models examined the multivariate prognostic validity of all assessments by predicting success with subjective (model 1), objective (model 2), and both groups of predictors (model 3). Confirming the univariate prognostic validity, future selected outperformed non-selected players regarding all predictors (each p < 0.001, except for agility in U15: p < 0.01). Tactical skills, kicking skills, and sprint were of highest predictive value (d ≥ 0.61 in each age group). Multivariate results provided empirical evidence for the subjective (7% ≤ Nagelkerke's R2 ≤ 11%; each p < 0.001) and objective (8% ≤ Nagelkerke's R2 ≤ 13%; each p < 0.001) assessments' prognostic validity. However, model 3 revealed the best statistical explanatory power in each age group (0.15 ≤ Nagelkerke's R2 ≤ 0.20; p < 0.001). In this combined assessment model, sprint, tactical skills, and dribbling were found to be the most predictive variables. In conclusion, this study reinforces the call for multidimensional diagnostics integrating objective and subjective assessments. Future research is needed to address the demands for longitudinal analyses of subjective ratings, the integration of biological maturation, and empirical evidence for female soccer.